ASEAN 2030: Challenges of building a mature political and security community - Amitav Acharya (Asian Development Bank Institute (ADBI), 2013)
This paper examines the political and security challenges and prospects of the Association of Southeast Asian Nations (ASEAN) in the coming two decades. To simplify what is a hugely complex and wide-ranging set of issues, I divide the security challenges facing ASEAN into six broad categories. These include (1) the shifting balance of power in the Asia Pacific region, triggered mainly, if not exclusively, by the dramatic rise of the People's Republic of China (PRC); (2) the persistence of intra-ASEAN territorial conflicts; (3) the territorial dispute in the South China Sea, which is a critical factor in PRC-ASEAN relations; (4) the programs of military modernizations undertaken by ASEAN states and the resulting prospects for an intra-ASEAN arms race; (5) uncertainty and strife caused by demands for domestic political change; (6) and the dangers posed by transnational (non-traditional) security threats. I argue that ASEAN faces major hurdles in realizing a mature political-security community, where intra-ASEAN tensions are significantly managed and reduced to the point where war becomes 'unthinkable' and a deep and genuine sense of regional community emerges. While recent steps undertaken by ASEAN are bold and far-reaching, realizing them would depend on several factors, especially the maintenance of its unity and cohesion in the face of a rising PRC, the ability to resolve regional disputes, complying with the provisions and instruments of the ASEAN Charter and the Political-Security Community Blueprint, and ensuring an agenda-setting and managerial role in the wider East Asian and Asia-Pacific multilateralism.
Keywords: F50; F51; F53; F55; 330; asean 2030; political security; community security; balance of power; territorial conflict; non-traditional security; asean-prc relations; Internationale Sicherheit; Politische Stabilität; Politischer Wandel; ASEAN-Staaten